2020
DOI: 10.1017/dmp.2019.156
|View full text |Cite
|
Sign up to set email alerts
|

Using Telemedicine in Mass Casualty Disasters

Abstract: Objectives: The goal of this study is to test an implementation and examine users’ perceptions about the usefulness of telemedicine in mass casualty and disaster settings and to provide recommendations for using telemedicine in these settings. Methods: Ninety-two US Army Forward Surgical Team (FST) members participated in a high-fidelity mass casualty simulation at the Army Trauma Training Center (ATTC). Telemedicine was implemented into this simulation. Results: Only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is encouraging to hear that a telemental intervention program designed to improve psychological problems in people who survived COVID-19 in Iran has led to statistically significant improvements in psychological symptoms over the follow-up period [ 16 ]. It is also worth noting that telepsychiatry is reliable and valid in several psychiatric disorders, and before the COVID-19 pandemic, evidence from studies had already indicated that it could improve mental disorders among adults [ 17 ]. The meta-analysis by Bolton et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging to hear that a telemental intervention program designed to improve psychological problems in people who survived COVID-19 in Iran has led to statistically significant improvements in psychological symptoms over the follow-up period [ 16 ]. It is also worth noting that telepsychiatry is reliable and valid in several psychiatric disorders, and before the COVID-19 pandemic, evidence from studies had already indicated that it could improve mental disorders among adults [ 17 ]. The meta-analysis by Bolton et al .…”
Section: Discussionmentioning
confidence: 99%
“…80 Hospital incident command may enable paediatric specialists to aid responders remotely through telemedicine, 81 although technological challenges may impede this assistance. 82,83 Incident command should ensure institutional preparation for the children it will receive, using its paediatric contingency plan as a guide. The participation of paediatric trauma centres may improve care in an MCI.…”
Section: Command and Controlmentioning
confidence: 99%
“…Telemedicine also facilitates diagnosis and treatment options when medical evacuation is impossible due to acute medical emergencies, mass casualty disasters, and public health measures (such as during COVID-19 pandemic restrictions) [18,19]. From a global health perspective, telemedicine increases the availability and quality of health care in remote areas and reduces medical inequalities between remote and urban areas [20][21][22][23][24]. Changes in the medical field have prompted concerns-how to achieve the optimal clinical outcome (ie, textbook outcome) in liver transplantation?…”
Section: Introductionmentioning
confidence: 99%